Curing treatment method for aluminum ash
By mixing aluminum ash with boron lithite and cone pyroxene, adding glass fiber and basalt fibers, using specific adhesives and plasticizers, refractory materials are prepared, which solves the low environmental pollution and resource utilization efficiency during aluminum ash treatment process. The problem of this problem has achieved efficient harmless treatment and resource utilization, and improved material performance.
Patent Information
- Application Number
- CN202411554611.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
AI Technical Summary
There is a risk of environmental pollution during the treatment process, and the prior art is difficult to effectively realize its harmless treatment and resource utilization, especially in terms of removing harmful components and improving resource utilization efficiency.
Aluminum ash is mixed with boron lithite and cone pyroxene, glass fiber and basalt fiber are added, and butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer are used as binders to combine and increase the Plasticizers and bonding agents are prepared by curing treatment to improve the refractory and mechanical properties of the material.
The harmless treatment and resource utilization of aluminum ash are achieved, environmental pollution is reduced, the refractory and mechanical properties of refractory materials are improved, and the cost of enterprises is reduced, and the efficient recycling and utilization of waste aluminum ash is achieved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resource utilization of aluminum ash, and specifically relates to a solidification treatment method for aluminum ash. Background Art
[0002] Aluminum ash is solid waste generated during the production process of the aluminum industry. It is mainly composed of metallic aluminum and aluminum oxide, and contains a large amount of valuable elements. According to the source and treatment process, aluminum ash can be divided into electrolytic aluminum ash, recycled aluminum ash and molten aluminum ash. Among them, primary aluminum ash is usually the residue left directly from the electrolytic aluminum production process, while secondary aluminum ash comes from various aluminum wastes. Aluminum ash has a high industrial recycling and reuse value, but it also poses environmental risks. Harmful components in aluminum ash, such as aluminum nitride, fluoride and chloride, are easy to leach. If improperly handled, they will cause pollution to the soil, groundwater and atmosphere. Therefore, how to harmlessly treat aluminum ash and utilize it as a resource has become an urgent problem to be solved.
[0003] At present, a variety of aluminum ash treatment technologies have been developed at home and abroad. For example, the innovative "one-stage dissolution + two-stage sintering" process of China Aluminum Corporation can harmlessly treat aluminum ash and realize high-value utilization. In addition, high-temperature decomposition technology is also used to produce calcium aluminate to achieve the reduction, resource utilization and harmlessness of aluminum ash. In practical applications, the treatment methods of aluminum ash include separation, precipitation and solidification technologies to remove harmful fluoride salts and other toxic substances. These technologies not only help reduce environmental pollution, but also recover valuable metallic aluminum and alumina. In short, as a hazardous solid waste, aluminum ash needs to take effective environmental protection measures for harmless treatment and resource utilization to protect the environment and improve resource utilization efficiency. Summary of the invention
[0004] The purpose of the present invention is to provide a method for solidifying aluminum ash.
[0005] A method for solidifying aluminum ash is carried out according to the following steps: (1) Grind the aluminum ash and pass it through a 200-400 mesh sieve; crush the ore and grind it and pass it through a 100-200 mesh sieve; mix the ground aluminum ash and ore powder in a mass ratio of (1-3):1 to prepare a mixture; (2) adding reinforcing fibers to the silicate aqueous solution, mixing evenly, then adding the mixture prepared in step (1), mixing evenly, and preparing a mixed slurry; (3) Heat the mixed slurry to 70-90°C, add adhesive, plasticizer and binder, stir for 20-40 minutes, pour into the mold, cool to room temperature and dry naturally.
[0006] The ore is a mixed ore in which pyroxene and pyroxene are mixed in a mass ratio of 2:1.
[0007] The mass concentration of silicic acid in the silicic acid aqueous solution is 20-30%.
[0008] The reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:1.
[0009] In step (2), the amount of reinforcing fiber added is 3-5% of the mass of the silicate solution, and the amount of the mixed material added is 40-60% of the mass of the silicate solution.
[0010] The adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:1.
[0011] The amount of the adhesive added is 10-20% of the mass of the mixed slurry.
[0012] The plasticizer is one or more of dibutyl phthalate, diisobutyl phthalate, dioctyl phthalate, and diisononyl cyclohexane 1,2-dicarboxylate.
[0013] The added amount of the plasticizer is 1-3% of the mass of the mixed slurry.
[0014] The binder is one or more of dextrin, pulp waste liquid, calcium lignin sulfonate and methyl cellulose.
[0015] The amount of the binder added is 1-3% of the mass of the mixed slurry.
[0016] Beneficial effects of the present invention: The present invention recycles the discarded aluminum ash and processes the discarded aluminum ash into refractory materials, which reduces the cost of enterprises and avoids the pollution of aluminum ash to the environment while processing solid waste. The combined use of boron lithium stone and cone pyroxene in the components improves the refractory performance of the refractory materials; the combined use of glass fiber and basalt fiber, the combined use of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer improves the mechanical properties of the materials. DETAILED DESCRIPTION
[0017] In order to facilitate understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0018] Example 1 A method for solidifying aluminum ash is carried out according to the following steps: (1) grinding aluminum ash and passing it through a 300-mesh sieve; crushing ore and grinding it, and passing it through a 150-mesh sieve; mixing the ground aluminum ash and ore powder in a mass ratio of 2:1 to prepare a mixed material; the ore is a mixed ore of boraxite and pyroxene in a mass ratio of 2:1; (2) adding reinforcing fibers to a 25% silicate aqueous solution, mixing the mixture evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:1; the amount of the reinforcing fibers added is 4% of the mass of the silicate aqueous solution, and the amount of the mixture added is 50% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 80°C, and an adhesive, dibutyl phthalate, and calcium lignin sulfonate are added, stirred for 30 minutes, poured into a mold, cooled to room temperature, and naturally dried; the adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:1; the amount of the adhesive added is 15% of the mass of the mixed slurry; the amount of the dibutyl phthalate added is 2% of the mass of the mixed slurry; and the amount of the calcium lignin sulfonate added is 2% of the mass of the mixed slurry.
[0019] Example 2 A method for solidifying aluminum ash is carried out according to the following steps: (1) grinding aluminum ash and passing it through a 200-mesh sieve; crushing ore and grinding it, and passing it through a 100-mesh sieve; mixing the ground aluminum ash and ore powder in a mass ratio of 1:1 to prepare a mixed material; the ore is a mixed ore of boraxite and pyroxene in a mass ratio of 2:1; (2) adding reinforcing fibers to a 20% silicate aqueous solution, mixing the mixture evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:1; the amount of the reinforcing fibers added is 3% of the mass of the silicate aqueous solution, and the amount of the mixture added is 40% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 70°C, and an adhesive, diisobutyl phthalate and dextrin are added, stirred for 20 minutes, poured into a mold, cooled to room temperature, and naturally dried; the adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:1; the amount of the adhesive added is 10% of the mass of the mixed slurry; the amount of diisobutyl phthalate added is 1% of the mass of the mixed slurry; and the amount of dextrin added is 1% of the mass of the mixed slurry.
[0020] Example 3 A method for solidifying aluminum ash is carried out according to the following steps: (1) grinding aluminum ash and passing it through a 400-mesh sieve; crushing ore and grinding it, and passing it through a 200-mesh sieve; mixing the ground aluminum ash and ore powder in a mass ratio of 3:1 to prepare a mixed material; the ore is a mixed ore of boraxite and pyroxene in a mass ratio of 2:1; (2) adding reinforcing fibers to a 30% silicate aqueous solution, mixing the mixture evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:1; the amount of the reinforcing fibers added is 5% of the mass of the silicate aqueous solution, and the amount of the mixture added is 60% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 90°C, and an adhesive, diisononyl cyclohexane 1,2-dicarboxylate and methyl cellulose are added, stirred for 40 minutes, poured into a mold, cooled to room temperature, and naturally dried; the adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:1; the amount of the adhesive added is 20% of the mass of the mixed slurry; the amount of diisononyl cyclohexane 1,2-dicarboxylate added is 3% of the mass of the mixed slurry; and the amount of methyl cellulose added is 3% of the mass of the mixed slurry.
[0021] Comparative Example 1 A method for solidifying aluminum ash is carried out according to the following steps: (1) Grind the aluminum ash and pass it through a 300-mesh sieve; crush the boron lithium stone and grind it, and pass it through a 150-mesh sieve; mix the ground aluminum ash and boron lithium stone powder in a mass ratio of 2:1 to prepare a mixture; (2) adding reinforcing fibers to a 25% silicate aqueous solution, mixing the mixture evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:1; the amount of the reinforcing fibers added is 4% of the mass of the silicate aqueous solution, and the amount of the mixture added is 50% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 80°C, and an adhesive, dibutyl phthalate, and calcium lignin sulfonate are added, stirred for 30 minutes, poured into a mold, cooled to room temperature, and naturally dried; the adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:1; the amount of the adhesive added is 15% of the mass of the mixed slurry; the amount of the dibutyl phthalate added is 2% of the mass of the mixed slurry; and the amount of the calcium lignin sulfonate added is 2% of the mass of the mixed slurry.
[0022] Comparative Example 2 A method for solidifying aluminum ash is carried out according to the following steps: (1) grinding aluminum ash and passing it through a 300-mesh sieve; crushing pyroxene and grinding it, and passing it through a 150-mesh sieve; and mixing the ground aluminum ash and pyroxene powder in a mass ratio of 2:1 to prepare a mixture; (2) adding reinforcing fibers to a 25% silicate aqueous solution, mixing the mixture evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:1; the amount of the reinforcing fibers added is 4% of the mass of the silicate aqueous solution, and the amount of the mixture added is 50% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 80°C, and an adhesive, dibutyl phthalate, and calcium lignin sulfonate are added, stirred for 30 minutes, poured into a mold, cooled to room temperature, and naturally dried; the adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:1; the amount of the adhesive added is 15% of the mass of the mixed slurry; the amount of the dibutyl phthalate added is 2% of the mass of the mixed slurry; and the amount of the calcium lignin sulfonate added is 2% of the mass of the mixed slurry.
[0023] Comparative Example 3 A method for solidifying aluminum ash is carried out according to the following steps: (1) grinding aluminum ash and passing it through a 300-mesh sieve; crushing ore and grinding it, and passing it through a 150-mesh sieve; mixing the ground aluminum ash and ore powder in a mass ratio of 2:1 to prepare a mixed material; the ore is a mixed ore of boraxite and pyroxene in a mass ratio of 2:1; (2) adding glass fiber to a 25% silicate aqueous solution, mixing evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the amount of the glass fiber added is 4% of the mass of the silicate aqueous solution, and the amount of the mixture added is 50% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 80°C, and an adhesive, dibutyl phthalate, and calcium lignin sulfonate are added, stirred for 30 minutes, poured into a mold, cooled to room temperature, and naturally dried; the adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:1; the amount of the adhesive added is 15% of the mass of the mixed slurry; the amount of the dibutyl phthalate added is 2% of the mass of the mixed slurry; and the amount of the calcium lignin sulfonate added is 2% of the mass of the mixed slurry.
[0024] Comparative Example 4 A method for solidifying aluminum ash is carried out according to the following steps: (1) grinding aluminum ash and passing it through a 300-mesh sieve; crushing ore and grinding it, and passing it through a 150-mesh sieve; mixing the ground aluminum ash and ore powder in a mass ratio of 2:1 to prepare a mixed material; the ore is a mixed ore of boraxite and pyroxene in a mass ratio of 2:1; (2) adding basalt fiber to a 25% silicate aqueous solution, mixing evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the amount of basalt fiber added is 4% of the mass of the silicate aqueous solution, and the amount of the mixture added is 50% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 80°C, and an adhesive, dibutyl phthalate, and calcium lignin sulfonate are added, stirred for 30 minutes, poured into a mold, cooled to room temperature, and naturally dried; the adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:1; the amount of the adhesive added is 15% of the mass of the mixed slurry; the amount of the dibutyl phthalate added is 2% of the mass of the mixed slurry; and the amount of the calcium lignin sulfonate added is 2% of the mass of the mixed slurry.
[0025] Comparative Example 5 A method for solidifying aluminum ash is carried out according to the following steps: (1) grinding aluminum ash and passing it through a 300-mesh sieve; crushing ore and grinding it, and passing it through a 150-mesh sieve; mixing the ground aluminum ash and ore powder in a mass ratio of 2:1 to prepare a mixed material; the ore is a mixed ore of boraxite and pyroxene in a mass ratio of 2:1; (2) adding reinforcing fibers to a 25% silicate aqueous solution, mixing the mixture evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:1; the amount of the reinforcing fibers added is 4% of the mass of the silicate aqueous solution, and the amount of the mixture added is 50% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 80°C, butene-1-ethylene copolymer, dibutyl phthalate and calcium lignin sulfonate are added, stirred for 30 minutes, poured into a mold, cooled to room temperature, and naturally dried; the amount of butene-1-ethylene copolymer added is 15% of the mass of the mixed slurry; the amount of dibutyl phthalate added is 2% of the mass of the mixed slurry; and the amount of calcium lignin sulfonate added is 2% of the mass of the mixed slurry.
[0026] Comparative Example 6 A method for solidifying aluminum ash is carried out according to the following steps: (1) grinding aluminum ash and passing it through a 300-mesh sieve; crushing ore and grinding it, and passing it through a 150-mesh sieve; mixing the ground aluminum ash and ore powder in a mass ratio of 2:1 to prepare a mixed material; the ore is a mixed ore of boraxite and pyroxene in a mass ratio of 2:1; (2) adding reinforcing fibers to a 25% silicate aqueous solution, mixing the mixture evenly, and then adding the mixture prepared in step (1), mixing evenly, to prepare a mixed slurry; the reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:1; the amount of the reinforcing fibers added is 4% of the mass of the silicate aqueous solution, and the amount of the mixture added is 50% of the mass of the silicate aqueous solution; (3) The mixed slurry is heated to 80°C, propylene-α-olefin-diene terpolymer, dibutyl phthalate and calcium lignin sulfonate are added, stirred for 30 minutes, poured into a mold, cooled to room temperature, and naturally dried; the amount of the propylene-α-olefin-diene terpolymer added is 15% of the mass of the mixed slurry; the amount of the dibutyl phthalate added is 2% of the mass of the mixed slurry; and the amount of the calcium lignin sulfonate added is 2% of the mass of the mixed slurry.
[0027] Experimental example: Refractory bricks were prepared according to the solidification treatment method of aluminum ash in Examples 1-3 and Comparative Examples 1-2, and the refractory brick 0.2MPa load softening temperature (T0.6) test was carried out in accordance with the "Test Method for Load Softening Temperature of Refractory Products (Non-Differential-Heating Method)" (YB / T 370-1995), Standard of the Ferrous Metallurgical Industry of the People's Republic of China.
[0028] SPSS 24.0 software was used for statistical analysis. The measurement data were expressed as x±s (mean ± standard deviation). The Kolmogorov-Smirnov test was used for data normality test. For data that met the normal distribution, the t test was used to compare the mean differences between the two groups. P<0.05 was considered statistically significant. The measurement results are shown in Table 1: Table 1
[0029] Note: * represents P < 0.05 compared with the group in Example 1.
[0030] Refractory bricks were prepared according to the solidification treatment method of aluminum ash in Examples 1-3 and Comparative Examples 3-6, and the compressive strength test was carried out in accordance with the National Standard of the People's Republic of China: Concrete Solid Bricks (GB / T 21144-2007). The test results are shown in Table 2: Table 2
[0031] Note: * represents P < 0.05 compared with the group in Example 1.
[0032] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for solidifying aluminum ash, characterized in that: Follow these steps: (1) Grind the aluminum ash and pass it through a 200-400 mesh sieve; crush the ore and grind it and pass it through a 100-200 mesh sieve; mix the ground aluminum ash and ore powder in a mass ratio of (1-3):1 to prepare a mixture; (2) adding reinforcing fibers to the silicate aqueous solution, mixing evenly, then adding the mixture prepared in step (1), mixing evenly, and preparing a mixed slurry; (3) Heat the mixed slurry to 70-90°C, add adhesive, plasticizer and binder, stir for 20-40 minutes, pour into the mold, cool to room temperature and dry naturally.
2. The method for solidifying aluminum ash according to claim 1, characterized in that: The ore is a mixed ore in which pyroxene and pyroxene are mixed in a mass ratio of 2:
1.
3. The method for solidifying aluminum ash according to claim 1, characterized in that: The mass concentration of silicic acid in the silicic acid aqueous solution is 20-30%.
4. The method for solidifying aluminum ash according to claim 1, characterized in that: The reinforcing fibers are glass fibers and basalt fibers mixed in a mass ratio of 1:
1.
5. The method for solidifying aluminum ash according to claim 1, characterized in that: In step (2), the amount of reinforcing fiber added is 3-5% of the mass of the silicate solution, and the amount of the mixture added is 40-60% of the mass of the silicate solution.
6. The method for solidifying aluminum ash according to claim 1, characterized in that: The adhesive is a mixture of butene-1-ethylene copolymer and propylene-α-olefin-diene terpolymer in a mass ratio of 3:
1.
7. The method for solidifying aluminum ash according to claim 1, characterized in that: The amount of the adhesive added is 10-20% of the mass of the mixed slurry.
8. The method for solidifying aluminum ash according to claim 1, characterized in that: The plasticizer is one or more of dibutyl phthalate, diisobutyl phthalate, dioctyl phthalate, and diisononyl cyclohexane 1,2-dicarboxylate.
9. The method for solidifying aluminum ash according to claim 1, characterized in that: The added amount of the plasticizer is 1-3% of the mass of the mixed slurry.
10. The method for solidifying aluminum ash according to claim 1, characterized in that: The binder is one or more of dextrin, pulp waste liquid, calcium lignin sulfonate, and methyl cellulose; the addition amount of the binder is 1-3% of the mass of the mixed pulp.
Citation Information
Patent Citations
Steam-curing-free high-strength aerated concrete material and preparation method of aerated concrete
CN113185318A
Preparation method for producing water purifying agent by using aluminum ash and application of water purifying agent
CN115974184A
Self-foaming geopolymer composition containing aluminum dross
US20160257616A1